Molecular epidemiology of Cryptosporidium spp. in North Lebanon - Marwan Osman; Sadia Benamrouz; Karine Guyot; Dima El Safadi; Hassan Mallat; Fouad Dabboussi; Monzer Hamze; Eric Viscogliosi; Gabriela Certad (Journal of Infection in Developing Countries)
Cryptosporidium spp. are enteroparasites with worldwide distribution that infect the gastrointestinal tract of several vertebrates including humans. Human to human, zoonotic, foodborne and waterborne are reported as the main transmission routes of this parasite. Cryptosporidium spp. have been recognized as the predominant cause of waterborne and foodborne outbreaks. However, the epidemiological situation of cryptosporidiosis is not well known in Lebanon, a developing country with a population often affected by intestinal parasitic infections.